B cell mechanosensing regulates ER remodeling at the immune synapse - Riobó, Isidora; Yuseff, María Isabel (Frontiers in Immunology, 2024)
Introduction Engagement of the B-cell receptor with immobilized antigens triggers the formation of an immune synapse (IS), a complex cellular platform where B-cells recruit signaling molecules and reposition lysosomes to promote antigen uptake and processing. Calcium efflux from the endoplasmic reticulum (ER) released upon BCR stimulation is necessary to promote B-cell survival and differentiation. Whether the spatial organization of the ER within the B-cell synapse can tune IS function and B-cell activation remains unaddressed. Here, we characterized ER structure and interaction with the microtubule network during BCR activation and evaluated how mechanical cues arising from antigen presenting surfaces affect this process. Methods B-cells were cultured on surfaces of varying stiffness coated with BCR ligands, fixed, and stained for the ER and microtubule network. Imaging analysis was used to assess the distribution of the ER and microtubules at the IS. Results Upon BCR activation, the ER is redistributed towards the IS independently of peripheral microtubules and accumulates around the microtubule-organization center. Furthermore, this remodeling is also dependent on substrate stiffness, where greater stiffness triggers enhanced redistribution of the ER. Discussion Our results highlight how spatial reorganization of the ER is coupled to the context of antigen recognition and could tune B-cell responses. Additionally, we provide novel evidence that the structural maturation of the ER in plasma cells is initiated during early activation of B-cells.